THE ORIENTATION OF ENTREPRENEURSHIP, INNOVATION CAPABILITIES, ACCESS TO FINANCING, AND THE APPLICATION OF DIGITAL TECHNOLOGY ON THE GROWTH AND SUSTAINABILITY OF MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMES) IN INDONESIA - Erizal Nazaruddin; Junet Kaswoto; Dwi Saleha; Irwan Irawadi Barus; Annuridya Rosyidta Pratiwi Octasylva (AKSELERASI: Jurnal Ilmiah Nasional, 2026)
This study examines the effects of entrepreneurial orientation, innovation capabilities, access to financing, and the application of digital technology on the growth and sustainability of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. Using a quantitative approach, data were collected from 175 MSME respondents through a Likert scale (1–5) questionnaire and analyzed using the Structural Equation Modelling-Partial Least Squares (SEM-PLS 3) technique. The results show that entrepreneurial orientation and innovation capabilities significantly and positively influence MSME growth, emphasizing that proactive and innovative business behavior enhances performance and competitiveness. Meanwhile, access to financing plays a vital role in supporting long-term sustainability, enabling MSMEs to maintain liquidity and expand operations. Furthermore, the application of digital technology demonstrates a significant impact on both growth and sustainability, suggesting that digital transformation strengthens market presence and operational efficiency. Collectively, these factors account for a substantial portion of the variance in MSME growth and sustainability, highlighting the interdependence between entrepreneurship, innovation, financial access, and technology adoption in shaping Indonesia’s MSME ecosystem.